Remunerasi Sebagai Kebijakan Kompensasi di Rumah Sakit Astrinapura Wonogiri, Provinsi Jawa Tengah - Prihatin, Sandyria, Drs. M. Farid Wajdi, MM., Ph.D, Ahmad Mardalis, SE., MBA (2014)
This study of the remuneration as compensation policy at the Hospital. The purpose of this study is to analyze the process of compensation and to analyze the application of remuneration as compensation policy. The data used in this thesis is the data associated with the implementation of the remuneration obtained from the documentation, interviews, and observations. The data collected was analyzed by qualitative descriptive analysis method. The results of this study indicate more clearly the compensation that is based on the employee's contribution to the work. Compensation in the form of structural policy benefits given equally to all office holders, the incentive is given in the form of incentives do not directly correspond to the index score of employees and direct incentives are given according to the number of services provided. The total income received by the employee in accordance with the increased contribution. With this remuneration it can be arranged in accordance with the teaching that the contribution of work, if the contribution is high then the income is high, if the contribution is low, a low income.